Aspectos organizacionales y de cooperación en I+D como criterios de clasificación: El caso de la industria alimentaria en la comunidad Valenciana - M. Sierra Pereiro; J. Albors Garrigós; M. E. Ruiz Molina (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2008)
The present paper addresses a proposal for a taxonomy of the local Valencia food industry by means of cluster analysis. This technique allows conforming conglomerates with similar characteristics which will facilitate its analysis and the design and application of public support policies contingent with the firms needs belonging to each cluster. In relation to factors and variables for the clusters conformation the following were emphasized: collaboration with university, firm size, existence of a dedicated R&D department as well as two factors associated with the firm competitiveness: skills at new product development and technology absorption capacity. Three distinctive conglomerates were found: leaders firms, innovators with potential for university collaboration and traditional conservative firms.
Keywords: 330; cluster; university-business relationship; food industry